Historical wig styling ancient Egypt to the 1830s - Lowery, Allison (Focal press costume topics series, 2013)
"Let Historical Wig Styling be your guide to creating beautiful, historically accurate hairstyles for your productions and events. Chapters begin with artwork of historic figures who influenced the look of each period. Detailed step by step instructions explain how to create their iconic hairstyles, which are illustrated by photographs showing the finished look from every angle. This volume covers hairstyles from Ancient Egypt through the Biedermeier style of the 1820s and 30s. Learn how to create hairstyles worn by: Ancient Egyptians, Medieval maidens, Ancient Grecians, Renaissance beauties, Ancient Romans, Georgian fops and so many more!"--Publisher.